Evaluation of higher cognitive functions following posterior quadrant disconnection in the non-dominant hemisphere: a Case Report - Kawase, Noeru; Nakae, Shunsuke; Kumon, Masanobu; Hayakawa, Motoharu; Shinzato, Chiaki; Sato, Yuriko; Uda, Takehiro; Mitsuhashi, Takumi; Fukunaga, Masaki; Ohba, Shigeo; Hirose, Yuichi (Frontiers in Human Neuroscience, 2025)
Posterior Quadrant Disconnection is a surgical technique designed to suppress seizure propagation while preserving motor and sensory functions in patients with drug-resistant epilepsy. Although seizure outcomes following this procedure have been reported, detailed evaluations of its impact on higher cognitive functions remain limited. This study aimed to assess the long-term seizure and cognitive outcomes following PQD in the non-dominant hemisphere, thereby evaluating the efficacy and safety of the procedure. In this case, the patient with drug-resistant epilepsy underwent preoperative evaluation using stereo electroencephalography (SEEG) to identify seizure onset zones and functional mapping related to visuospatial cognition. Following this assessment, PQD was performed. Postoperative outcomes were monitored over a 2-years period, focusing on seizure control and higher cognitive function. The patient achieved Engel class I status postoperatively, indicating complete seizure cessation. While transient hemispatial neglect was observed immediately after surgery, gradual improvement was noted over time. Furthermore, visual memory and cognitive functions showed a tendency to improve, and there were no significant declines in facial recognition or scene recognition abilities. These findings suggest that PQD can effectively improve seizure outcomes while minimizing long-term impacts on cognitive functions. This case highlights the potential of PQD to offer substantial seizure control with limited permanent effects on higher cognitive functions. By providing valuable insights into the safety and efficacy of PQD in the non-dominant hemisphere, this study underscores its viability as a treatment option for selected cases of drug-resistant epilepsy.